Mitigation of diffuse water pollution from agriculture in England and China, and the scope for policy transfer. (February 2017) - Smith, Laurence; Inman, Alex; Lai, Xin; Zhang, Haifang; Fanqiao, Meng; Jianbin, Zhou; Burke, Sean; Rahn, Clive; Siciliano, Giusippina; Haygarth, Philip M.; Bellarby, Jessica; Surridge, Ben
Highlights: Policy framework for mitigation of diffuse water pollution from agriculture defined. Constraints to policy transferability defined and evaluated. Options for regulation, incentive payments, advice and voluntary action. Extension-led diffuse water pollution mitigation strategies recommended. Abstract: This paper evaluates the existing policy frameworks for mitigation of diffuse water pollution from agriculture (DWPA) in England and China. With reference to a conceptual model of the process of policy transfer or international lesson drawing, and possible constraints to this, it assesses whether and how China can draw lessons to improve current policy from the supra-national and national provisions of the EU and a member state that by 2016 had comprehensively implemented EU agricultural and environmental policy. DWPA is first analysed as a public policy challenge to inform specification of a generic framework for its mitigation. The current policy frameworks for mitigation of DWPA in England and China are evaluated, and their potential for improvement is assessed. A number of barriers to lesson drawing for regulation, incentive payments schemes and advice provision are diagnosed. These barriers are potentially least in relation to advice provision and its use to promote voluntary action by farmers. Given its structure and capabilities the public agricultural extension system in China is also recognised as a key resource. A focus on three policy approaches to mitigate DWPA in China is recommended: i) targeted regulation to a 'reference level' of large intensive livestock, and ultimately other large commercial farms; ii) strategic use of incentive payment schemes to protect water resources from DWPA; and iii) re-orientation of the ethos and modalities of operation of the extension system, informed by international lesson drawing, with the aim of rebalancing farm productivity and environmental protection.